MODEL PROBLEM-BASED LEARNING PADA MATERI SISTEM PENCERNAAN PADA MANUSIA: SUATU STUDI PADA SISWA SMA NEGERI 2 TONDANO - Willem, Alfiani; Naharia, Orbanus; Tengker, Anita C.C. (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to evaluate the effectiveness of applying the Problem-Based Learning (PBL) model in improving student learning outcomes on the ecosystem material at SMA Negeri 2 Tondano. This study uses a Classroom Action Research (CAR) design with two cycles, involving 30 students in the experimental class using the PBL model and 30 students in the control class applying a conventional learning model based on discussions and question-and-answer sessions. Data were collected through affective observations and cognitive evaluations using posttests at the end of each cycle. The results of the study show that the PBL model can improve student learning outcomes in both cognitive and affective domains. In the cognitive domain, the classical completeness percentage increased from 80% in Cycle I to 100% in Cycle II, with the average class score increasing from 80.15 to 90.35. In the affective domain, all students showed significant improvement, with observation scores in the high category in both cycles. The application of the PBL model motivated students to be more actively engaged in learning and improved their positive attitudes, such as discipline, responsibility, and self-confidence. This study shows that the PBL model is effective in improving both cognitive understanding and affective development in students. These findings suggest that applying PBL in Biology learning can improve the quality of teaching and student learning outcomes, with important implications for the development of problem-based teaching methods in schools